New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper focuses on gaps and multiplier effects of infrastructure investment in New Zealand. There has been high quality work done to quantify the infrastructure gap for New Zealand by Oxford Economics on behalf of the Global Infrastructure Hub, drawing on international experiences and local data sources, but recognizing the risk that the infrastructure gap may be even larger than that stated in this work. This paper provides further analysis about the effects on New Zealand's economy of closing the infrastructure gap. Closing the gap has quantifiable benefits, not just because it is a short-term stimulus to aggregate demand, but because of longer-lived effects on productivity, benefiting all sectors of the economy. There are prospective gains from closing New Zealand's infrastructure gap. New Zealand has improved its infrastructure spending in the past several years. Nonetheless, there is scope to expand it further, to reduce its (admittedly small, but probably understated) infrastructure gap to match other advanced economies, and possibly help with regional development concerns.